Performance, Methane Emission, Nutrient Utilization, and the Nitrate Toxicity of Ruminants with Dietary Nitrate Addition: A Meta-analysis from In Vivo Trials - Abdelbagi, M.; Ridwan, R.; Fitri, A.; Nahrowi; Jayanegara, A. (Tropical Animal Science Journal, 2023)
This study aims to evaluate the effects of dietary nitrate addition on performance, methane emission, nutrient utilization, and the nitrate toxicity of ruminants by using the meta-analysis methodology from in vivo trials. A total of 38 published papers and 139 studies were used. Parameters observed were feed intake, animal performance, enteric methane emission, and nitrate toxicity. Data were subjected to the mixed model methodology. Nitrate doses or forms were treated as fixed factors, while the different studies were treated as random factors. Results revealed that nitrate supplementation significantly decreased the milk protein content, milk fat content, dry matter intake, gross energy intake, the molar proportion of the propionic acid, methane production, and the metabolism of vitamin A in a linear pattern (p